Influence of coadsorbates on the NO dissociation on a rhodium(311) surface. - Inderwildi, O; Lebiedz, D; Deutschmann, O; Warnatz, J (2005)
Density functional theory (DFT) studies were performed to investigate the influence of coadsorbates on the nitrogen oxide dissociation on the vicinal rhodium(311) surface. This study amplifies prior studies on the dissociation of oxygen and nitrogen oxide on the (111) facet of rhodium. The influence of coadsorbates on the kinetic parameters and thermochemistry of the NO dissociation on Rh311 was studied. In addition, the activation energy and thermochemistry of this reaction were determined as a function of oxygen preoccupation/initial coverage. Steric and electronic effects and their influence on the dissociation reaction were examined. The results are discussed in the face of an NOx dissociation catalyst system proposed by Nakatsuji.